The Effect audit pricing on earnings management among non-financial listed firms in Nigeria. - Olajide, Fatimat; Olowookere, Johnson K.; Adebayo, A. O.; Oladejo, T. M. (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
This study investigates the effect of audit pricing, measured through normal and abnormal audit fees, on real earnings management (REM) in Nigerian non-financial listed firms. Using panel data from 50 firms listed on the Nigerian Exchange Group between 2013 and 2022, and employing Roychowdhury’s (2006) real earnings management model, the study finds a statistically significant negative relationship between normal audit fees and REM, β = -0.046, p = 0.0113. This suggests that higher audit fees, reflecting better audit quality and effort, deter managerial manipulation of earnings. Audit tenure also negatively correlates with REM, indicating that longer auditor-client relationships may enhance audit effectiveness. However, firm age, size, and loss indicators show no significant impact. The findings support agency theory’s premise that adequate audit remuneration mitigates agency conflicts by constraining managerial opportunism. Despite some contrasting literature, results emphasize the strategic importance of fair audit pricing to uphold financial reporting integrity. The study recommends that regulators enforce guidelines ensuring fair audit pricing linked to service quality, companies invest in high-quality audits as part of good governance, and auditors promote transparency in fee attribution to reinforce audit credibility. This research contributes empirical evidence to the nuanced relationship between audit fees and earnings management in emerging markets like Nigeria, highlighting audit pricing as a critical mechanism for enhancing audit quality and financial reporting transparency.